Personal qualities and career longevity of elite Latvian athletes - Eikena, D.; Iancheva, T. (Journal of Applied Sports Sciences, 2024)
In recent years, sports psychology researchers have shown a growing inter est in exploring various facets of sports careers, career transitions, the personal qualities profi le of athletes who achieve peak sports performance, and the exist ing models and distinctions within career stages.This research aimed to examine the link between the mental qualities and skills and the sports careers of elite Latvian athletes and to seek potential dif ferences dependent on sports career stages, level of qualifi cation, and gender. The research was done among 109 elite athletes from Latvia aged 17 to 40, practicing 19 sports - 71 men and 38 women. For the purposes of the research, the subjects were divided into groups according to two criteria: 1) depending on the diff erent stages of their sports career and 2) depending on the type of development of their sports career. The research methods included: Latvian personality survey (LPA-v3, Perepjolkina et al., 2011); Sports et al. (SMTQ; Sheard et al., 2009), adapted for Latvian conditions by Astafi cevs et al. (2020); Psychological Performance Inventory Alternative version (PPI-A; Golby et al., 2007), adapted for Latvi an conditions by Astafi cevs et al. (2020.); General et al. (GSE; Schwarzer & Jerusalem, 1995), adapted for Latvian conditions by Astafi cevs et al. (2020); Psychological Skills Inventory for Sports (PSIS-R5), adapted for Latvian con ditions by Fernate Andra, 2008.The obtained results revealed some diff erences in the personal profi les of the Latvian athletes depending on the stages and type of their sports careers, level of qualifi cation, and gender. We found higher results along the factors conscientiousness, honesty and modesty, and the lowest results along the factor neuroticism among the elite athletes. We found signifi cantly higher values of the mental skills: anxiety control, concentration, mental preparation, motivation, self-confi dence, and control among the men.